Synthetic Strategies and Applications of GaN Nanowires - Guoquan Suo; Shuai Jiang; Juntao Zhang; Jianye Li; Meng He (Advances in Condensed Matter Physics)
GaN is an important III-V semiconductor material with a direct band gap of 3.4 eV at 300 K. The wide direct band gap makes GaN an attractive material for various applications. GaN nanowires have demonstrated significant potential as fundamental building blocks for nanoelectronic and nanophotonic devices and also offer substantial promise for integrated nanosystems. In this paper, we provide a comprehensive review on the general synthetic strategies, characterizations, and applications of GaN nanowires. We first summarize several growth techniques of GaN nanowires. Subsequently, we discuss mechanisms involved to generate GaN nanowires from different synthetic schemes and conditions. Then we review some characterization methods of GaN nanowires. Finally, several kinds of main applications of GaN nanowires are discussed.